Reduced cortical thickness in World Trade Center responders with cognitive impairment: Neuroimaging / differential diagnosis. (7th December 2020) - Clouston, Sean; Deri, Yael; Horton, Megan; Tang, Cheuk; Diminich, Erica D; Pellecchia, Alison; Carr, Melissa; Gandy, Samuel; Sano, Mary; Bromet, Evelyn; Lucchini, Roberto; Luft, Benjamin
Abstract: Background: Recent reports suggest that World Trade Center (WTC) responders are at increased risk for cognitive impairment (CI). The current study utilized neuroimaging to determine whether WTC responders with CI have reduced cortical thickness (CTX). Method: WTC responders (N=99) with and without CI, recruited from an epidemiologic study of cognitive aging among WTC responders, participated in a neuroimaging study that included a T1‐MPRAGE protocol. CTX was computed in 34 Desikan‐Killiany atlas regions of interest (ROIs). Regional CTX between CI and non‐CI responders were compared using t‐tests and reported using Cohen's D, and whole‐brain surface‐based morphometry using threshold‐free cluster analysis. Sensitivity analyses were used to examine possible associations of CTX with symptoms of PTSD and/or severity of WTC exposure. Analyses were adjusted for multiple comparisons using the false discovery rate (FDR = 0.05). Results: Participants were aged 55.84 years on average, and 47 had CI as determined by clinical mental status examination using the Montreal Cognitive Assessment (MoCA≤20). When compared to unimpaired responders, responders with CI had reduced mean whole‐brain CTX (P = 0.002). Region‐based analyses identified reduced CTX in 21/34 bilateral ROIs (D = ‐0.60) with the largest effects centered in the precentral gyrus (D = ‐0.74, P = 0.007). Surface‐based morphometry revealed that CTX was reduced across large parts of the frontal, temporal, and occipital lobes, all of which remained significant following adjustment for multiple comparisons. While more regions were identified as reduced in responders with both PTSD and CI (18 versus 9 ROIs in responders with PTSD and CI versus CI alone respectively), sensitivity analyses were not able to distinguish CI with PTSD as compared to CI alone. Conclusions: Results from structural imaging revealed that WTC responders with CI had reduced cortical thickness across multiple brain regions including but not limited to those commonly affected by Alzheimer's disease. This study represents the first neuroimaging study investigating CTX as an indicator of CI in WTC responders at midlife.